The Impact of Cold Ischaemia Time on Outcomes of Living Donor Kidney Transplantation in the UK Living Kidney Sharing Scheme. Issue 5 (November 2021) - van de Laar, Stijn C.; Robb, Matthew L.; Hogg, Rachel; Burnapp, Lisa; Papalois, Vassilios E.; Dor, Frank J. M. F.
Abstract : Objective: To assess the impact of CIT on living donor kidney transplantation (LDKT) outcomes in the UKLKSS versus outside the scheme. Background: LDKT provides the best treatment option for end-stage kidney disease patients. end-stage kidney disease patients with an incompatible living donor still have an opportunity to be transplanted through Kidney Exchange Programmes (KEP). In KEPs where kidneys travel rather than donors, cold ischaemia time (CIT) can be prolonged. Methods: Data from all UK adult LDKT between 2007 and 2018 were analysed. Results: 9969 LDKT were performed during this period, of which 1396 (14%) were transplanted through the UKLKSS, which we refer to as KEP. Median CIT was significantly different for KEP versus non-KEP (339 versus 182 minutes, P < 0.001). KEP LDKT had a higher incidence of delayed graft function (DGF) (2.91% versus 5.73%, P < 0.0001), lower 1-year (estimated Glomerular Filtration Rate (eGFR) 57.90 versus 55.25 ml/min, P = 0.04) and 5-year graft function (eGFR 55.62 versus 53.09 ml/min, P = 0.01) compared to the non-KEP group, but 1- and 5-year graft survival were similar. Within KEP, a prolonged CIT was associated with more DGF (3.47% versus 1.95%, P = 0.03), and lower graft function at 1 and 5-years (eGFR = 55 vs 50 ml/min, P = 0.02), but had no impact on graft survival. Conclusion: Whilst CIT was longer in KEP, associated with more DGF and lower graft function, excellent 5-year graft survival similar to non-KEP was found. Abstract : Supplemental Digital Content is available in the text